(3QSGdI aj TQH GdONGfs - (3GdMSjfj, GdNGOej, GdfbTHfOj, GdMfaj, CHh SYjO, eMeO Hf eUWai Hf YKeGf, J (B1176 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO dhdjg hGdUdGI Ydi fHjg hBdg hHYO aCeQ GdONGf cKQ ajg GdaJGhi hGdbjd hGdbGd hCda ajg GdQSGFd GdbUGQ hGdWhGd aGaJJf ajg GdCfGe hJMjQ GdNhGU hGdYhGe EP PgH HYV Ydi EHGMJg (B( (3cPG (B) (3hHYV Ydi MXQjJg aJHjf GdMb EfeG jchf HHjGf COdI GdaQjbjf (B--s
(3BNQgG (B:s
(3hCeG aj HYV GdehGVY ef QhGjI GdMOjK Yf HYV GdJaGSjQ aGdXGgQ Cfg eeG dG jbhd Ydjg fYe dh de jbY HhVYg hhbY aj EMJjGW TjA ef GdCMcGe ajQLM GdYed HGdMOjK GdVYja hCf de jhLH ceG fbd Yf CPcGQ Gdfhhjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 68s
(3eYLe GdeDdajf (B3 / 692s
(3gOjI GdYGQajf (B2/ 333s
(3eYLe GdeWHhYGJ (B808s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs